Keterampilan Pengungkapan Diri (Self-Disclosure) Bagi Siswa SMA Negeri Tompaso Baru - Mangantes, Meisie Lenny (Jurnal Ilmiah Wahana Pendidikan, 2023)
One type of social skill is self-disclosure skills. As a result of the lack of ability to express themselves, teenagers do not have close friends, become less familiar with their friends, and worse still are isolated from their friends. It is hoped that this self-disclosure training can help students recognize and manage the emotional problems they experience. Therefore, self-disclosure skills training is considered very important for Tompaso Baru State High School. The method of implementing this service uses training techniques. The result of self-disclosure training is an effort to provide guidance to Tompaso Baru State High School students who are able to have abilities in terms of social skills. Participants who took part in this training were declared successful because they demonstrated 90% mastery of knowledge and skills in self-disclosure.